Factors influencing childhood immunization uptake in Africa: a systematic review - Galadima, Abubakar Nasiru; Mohd Zulkefli, Nor Afiah; Md Said, Salmiah; Ahmad, Norliza (BioMed Central, 2021)
Vaccine preventable diseases are still the most common cause of childhood mortality, with an estimated 3 million deaths every year, mainly in Africa and Asia. An estimate of 29% deaths among children aged 1–59 months were due to vaccine preventable diseases. Despite the benefits of childhood immunisation, routine vaccination coverage for all recommended Expanded Programme on Immunization vaccines has remained poor in some African countries, such as Nigeria (31%), Ethiopia (43%), Uganda (55%) and Ghana (57%). The aim of this study is to collate evidence on the factors that influence childhood immunisation uptake in Africa, as well as to provide evidence for future researchers in developing, implementing and evaluating intervention among African populations which will improve childhood immunisation uptake.